Safe construction for the future proceedings of a conference organized by the Institution of Civil Engineers and held in London on 29 January 1980. (Institution of Civil Engineers, 1980)
Concluding with a discussion on every paper, this work focuses on the interface between the designer and the contractor and safety problems involved, health hazards in the construction industry, human behaviour, management and safety, contracts and legislation, and industrial relations, trade unions and safety representatives.